Listening to the Musical Argument - Llidó Vicent, Maria (Res Publica. Revista de Historia de las Ideas Políticas, 2014)
This text seeks to bring out some of the implications of a musical turn of philosophy pointed by Eugeio Trías. This turn has been carried out also by authors such as Jean-luc Nancy and Marie-Louise Mallet, who consider the possibility of a sense not based on the logical order of discourse, but understood as an event of nature almost tactile. The sonority allows us to open a space for listening on the threshold of the sense, so that in this space is given a different genesis that enables the implementation in a resonance of the understanding between the subject and the world. thus, the philosophy begins to listen to the sonority and to think attending to the music.
Keywords: event; listening; musical turn; sonority; tactile.